MANAJEMEN PENGELOLAAN SUMBER DAYA DALAM MENINGKATKAN AKADEMIK DI SEKOLAH DASAR NEGERI 2 BAKARUNG SELATAN KABUPATEN HULU SUNGAI SELATAN - Sri Hartini; Muhammad Yuliansyah; Didi Susanto (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study seeks to explore and evaluate resource management in efforts to enhance student academic performance at SDN 2 Bakarung Selatan, South Hulu Sungai Regency. The study is motivated by low student academic outcomes, which are believed to be linked to less-than-optimal management of educational resources, including human resources, facilities and infrastructure, as well as school finances. A descriptive qualitative approach was employed, with data gathered through observation, in-depth interviews, and document analysis. The findings reveal that resource management at SDN 2 Bakarung Selatan involves three main stages. First, the planning stage is still largely formal and does not fully engage all stakeholders. Second, the implementation stage faces challenges such as teacher competency issues, limited learning facilities, and the suboptimal use of BOS funds to enhance academic quality. Third, the evaluation stage is not carried out in a systematic or continuous manner. The principal plays a central role as a learning leader, motivating all school components to collaborate synergistically and participatively. This study highlights the necessity of integrated and context-sensitive resource management, especially in public elementary schools located in rural areas. Key strategies include enhancing teacher competencies, optimizing the use of facilities, and allocating budgets with a focus on improving learning quality. The results are expected to provide insights for the formulation of more effective educational policies and managerial practices in elementary schools.